2009
DOI: 10.1111/j.1540-8167.2008.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Electrogram Guided Substrate Ablation Add to the Success of Pulmonary Vein Isolation in Patients with Paroxysmal Atrial Fibrillation? A Prospective, Randomized Study

Abstract: In the intention-to-treat analysis, additional CFAE ablation did not improve the success rate of PVI in patients with paroxysmal AF. However, during long-term follow-up, patients with still inducible AF after PVI seemed to profit from additional CFAE ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 31 publications
3
56
0
1
Order By: Relevance
“…7,[15][16][17][18][19][20][21] A careful review of their reference list provided 4 more entries that were selected after revision of the full text. [22][23][24][25] Manual searches also provided 1 last entry, a randomized controlled trial recently published in a Hot-Line Session at a major cardiovascular meeting. 8 The selection process is illustrated in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,[15][16][17][18][19][20][21] A careful review of their reference list provided 4 more entries that were selected after revision of the full text. [22][23][24][25] Manual searches also provided 1 last entry, a randomized controlled trial recently published in a Hot-Line Session at a major cardiovascular meeting. 8 The selection process is illustrated in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Some studies used automatic algorithms incorporated into 3-dimensional mapping systems, 7,8,16,18,20,24 whereas others relied on operator-guided analysis of electrograms. 15,17,19,[21][22][23]25 Data about outpatient treatment, relapse definition, and follow-up in the different studies are shown in Table 3. Mean follow-up duration was >12 months in the majority of studies.…”
Section: What Is Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been further proposed that these fractionated sites are important in sustaining AF, 53 and that targeting fractionated electrograms with ablation can terminate AF and prevent its re-induction or recurrence. 52,[54][55][56][57][58][59][60] The data supporting these conclusions are rather weak overall, with only a few small, randomised clinical trials providing guidance, and different studies have arrived at disparate conclusions regarding the importance, or lack thereof, of fractionated electrograms in the pathogenesis of AF.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 96%
“…Full text assessment of the 10 potentially relevant articles resulted in 7 eligible controlled studies ( Figure 1). The reasons for exclusion were as follows: CFAEs ablation was used as a stand-alone strategy for AF ablation 11 ; data of sinus rhythm maintenance after 1 ablation procedure was not offered 12 ; the sites of additional CFAE ablation formed lines along the left atrial septum, roof, posterior mitral annulus, and/or anterior wall, therefore the CFAE ablation was in fact linear ablation procedure. 13 Eventually, 7 trials with a total of 662 subjects were included in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%